Experimental validation of a novel architecture based on a dual-stage converter for off-board fast battery chargers of electric vehicles - Monteiro, Vítor Duarte Fernandes (2018)
The experimental validation of a novel architecture of an off-board, three-phase fast battery charger for electric vehicles (EVs) with innovative operation modes is presented in this paper. The proposed EV fast battery charger is based on a dual-stage power converter (ac-dc and dc-dc) sharing the same dc link. The ac-dc stage is used as an interface between the power grid and the dc link. It is composed of the parallel association of two full-bridge voltage-source converters, and allows control of the grid current and of the dc-link voltage. The dc-dc stage is used as an interface between the dc link and the batteries. It is constituted by a bidirectional three-level asymmetrical voltage-source converter, and controls the flux of current during the EV battery charging process. Compared with the traditional solutions used for EV fast battery chargers, the proposed architecture operates as an interleaved converter, facilitating the reduction of the passive filters size, and the grid current harmonic distortion for the same switching frequency. Throughout the paper, the ac-dc and dc-dc stages, and the digital control algorithms are described in detail. The experimental validation was performed in a laboratory using a developed EV fast battery charger prototype, operating through the grid-to-vehicle and the proposed charger-to-grid modes, exchanging active, and reactive power with the power grid.